На пути к «морали ценности». Рыцарская топика или аксиология нового рыцарства – опыт соотнесения: "Бедный рыцарь" Елены Гуро и "Рыцарь кубков" Терренса Малика - Mielniczuk, Jekatierina (Acta Neophilologica, 2022)
The subject of the research was E. Guro’s novelThe Poor Knight and T. Malick’s film Knight of the Cups. The analysis, inspired N. Bierdiayev’s reflections on the “ethics of values” and the concept of “new knighthood”, indicates the dialogical relations between distant texts of culture. The comparative analysis reveals the following: 1. Guro introduces a new type of literary hero that has a palimpsest character; 2. updates the axiological sense of the knight; 3. the continuity of the knight’s ethos is brought out by the analogy to Malick’s film – their “common places” are: the initiation scheme, the Master / teacher archetype, and the concept of a knight’s mission.